(3GdedNU (B((3edNU GdbhGfjf aj GdfMh(B)s - (3CHhGdMSjf YHjO Gddg Hf CMeO Hf YHjO Gddg GHf CHj GdQHjY GdbQTj GdCehj GdYKeGfj GdGTHjdj,J (B688 (3g` s ((3eMeO Hf YjGO Hf eMeO GdbQTj GdeNRhej s)
(3ChdgG (B:s
(3HGH GdLQ(B: (3GdLQ dG jchf EdG HGdEVGaI hGdEVGaI Ydi hLgjf(B: (3CMOgeG EVGaI GdaYd Edi GdGSe s
(3BNQgG (B:s
(3hEOZGegG aj Gdfhf Cbd eeG PcQ, hEfeG bd dCf Gdfhf JOZe aj NeSI CMQa ceG JbOe s
(3GdSaQ GdKGfj hjTJed Ydi HbjI GdLRA GdChd hGdLRA GdKGfj cdg ef JLRFI GdeDdas
(3Ydi GdfSNI ebGHdIs
(3fSNI KGfjI JJab aj BNQgG eY BNQ GdfSNI GdChdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B191s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B547 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B313 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1819s
Keywords: (3GdfMhs